The educative and scalable functions of authoring tools to support inquiry-based science learning - Saballus, Ulf; Asher, Itay; Nasser, Samira; Ganaim, Lina; Tabak, Iris; Kollias, Vassilis P.; Iolie Nicolaidou; Terzian, Frederiki; Hadjichambis, Andreas Ch.; Kafouris, Dimitris; Redfors, Andreas; Hansson, Lena; et al. (My University, 2010)
Specialized authoring tools enable non-programmers to develop computer-based learning environments that reflect a particular task model. Large-scale implementation of novel but pedagogically sound environments is made possible if the resulting environments reflect the intended essential pedagogical features. We explore the balance between constraints and generativity through five teams' experiences with a specialized authoring tool, STOCHASMOS. We hope to spark a critical discussion of the role of specialized authoring tools in scalability. We also suggest that future research examine the educative function of these tools. ISLS.
Keywords: Computer aided instruction; Authoring tool; Computer-based learning environments; Critical discussions; Generativity; Inquiry-based science; Pedagogical features; Scalable functions; Sound environment